1,000 practice MTF MCQs for the primary and final FRCA - Ebrahim, Hozefa (Cambridge : Cambridge University Press, 2019)
"Atrial contraction accounts for 10% of ventricular filling at rest. At high heart rates this ratio increases to 40% due to limited time available for passive filling. After atrial contraction is complete, the atrial pressure starts to fall. This causes the valve to float upwards before closure. At this time the ventricular volume is maximal, which is termed the End Diastolic Volume (EDV). The two main coronary arteries are the left main and right coronary arteries. The left main coronary artery supplies blood to the left side of the heart muscle (the left ventricle and left atrium). The right coronary artery supplies blood to the right ventricle, the right atrium, and the SA (sinoatrial) and AV (atrioventricular) nodes, which regulate the heart rhythm. Each cardiac myocyte is surrounded by a cell membrane called the sarcolemma and contains one nucleus. The cells are packed with mitochondria to provide the steady supply of ATP required to sustain cardiac contraction. As with skeletal muscle, cardiac myocytes contain the contractile proteins actin (thin filaments) and myosin (thick filaments) together with the regulatory proteins troponin and tropomyosin. Cardiac muscle is striated, although the pattern is not as ordered as in skeletal muscle"--Provided by publisher.
Includes index.
Keywords: Royal College of Anaesthetists (Great Britain); Anesthesia -- methods; Anesthetics -- pharmacology; United Kingdom; Examination Questions